The distinct role of kappa opioid receptor in attenuating relapse to morphine/methamphetamine (polydrug) dependence in mice - Irna Elina Ridzwan; Maryam Saadah Suhaimi; Nur Syafinaz Wasli; Abdul Razak Kasmuri; Marwan Saad Azzubaidi; Ridzwan Hashim; Qamar Uddin Ahmed; Long Chiau Ming; Nornisah Mohamed; Syed Mohd Syhami (University of Huddersfield Press, 2018)
A Combination of 0.3mg/kg buprenorphine and 1.0 mg/kg naltrexone treatment shows a promising result due to its ability to attenuate reinstatement (relapse) in morphine/methamphetamine (polydrug)-dependent mice in a conditioned place preference (CPP) model. This prompted us to identify which opioid receptor that contributes to its anti-relapse activity. Using the same CPP model, 10 mg/kg nor- BNI (a selective kappa opioid receptor [KOR] antagonist) was used to evaluate the involvement of KOR in mediating relapse to polydrug dependence. By applying the immunohistochemistry (IHC) technique, the investigation was extended to the mice brain using KOR antibody (EPR18881), focusing on the brain regions that are abundant in KOR density. The results showed that nor-BNI alone failed to attenuate relapse to polydrug dependence. However, the IHC results proved that the number of KOR significantly increased in the striatum during reinstatement compared to post-conditioning (p <0.05). The KOR was significantly suppressed in the treatment group which strengthens the findings from previous studies proving that the KOR plays an important role in mediating relapse to polydrug dependence.